Digital Gangrene: An Unusual Manifestation of Non-Hodgkin Lymphoma - Muhammad Shoaib Momen Majumder; Shamim Ahmed; Tajkia Haque; Syed Atiqul Haq; Saumitra Chakravarty; Md. Abu Shahin; Din-E-Mujahid Mohammad Faruque Osmany; Johannes J. Rasker (Case Reports in Vascular Medicine)
Background. Non-Hodgkin lymphomas (NHLs) comprise a group of haematologic malignancies with different histologic subtypes. The clinical picture varies from indolent to aggressive presentation and nodal (lymphadenopathy) to extranodal (central nervous system, gastrointestinal, cutaneous plaque, or ulcer) involvement. Digital gangrene is seldom reported. Here, we describe a patient with pain and blackening of all fingers and toes as presenting symptoms of NHL. Case Presentation. A 32-year-old male weaver had been smoking three to five cannabis-containing cigarettes daily for about ten years and methamphetamine four to five tablets daily for five years. He had no history of Raynaud’s phenomenon, fever, cough, weight loss, skin rash, joint pain, and atherogenic or thrombogenic risk factors. We found normal blood pressure and absent peripheral pulses in arms and legs, dry gangrene of all fingers and toes, generalized lymphadenopathy, and hepatomegaly with ascites. The chest X-ray was normal, as were blood sugar, lipid profile, and hepatic and renal function. Rheumatoid factor, antinuclear and antiphospholipid antibodies, C-ANCA and P-ANCA, hepatitis B and C, and HIV were negative. CT abdomen revealed hepatosplenomegaly with multiple intra-abdominal lymphadenopathies. The peripheral angiogram showed 90-99% stenosis of radial and dorsalis pedis arteries with normal proximal vessels. Diagnosis of non-Hodgkin lymphoma was confirmed by histopathology of cervical lymph node (diffuse type), immunohistochemically subtyped as peripheral T cell lymphoma (not otherwise specified). The digital ischemia worsened despite cessation of cannabis and methamphetamine and starting CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisolone) treatment, making amputation necessary. Conclusion. We present, to our knowledge, the first report of peripheral T cell lymphoma, NOS presenting with gangrene in all digits complicated by methamphetamine and cannabis abuse. This uncommon vascular manifestation of non-Hodgkin lymphoma may cause a diagnostic dilemma and delayed initiation of treatment.